Le Haut DadÃ¨s: Un Site Montagnard De Grande Valeur Touristique - Aafir, Mustapha; Sabiri, Aboubakr (European Scientific Journal, ESJ, 2018)
Dades is a unique valley, defined by a long green oasis covering the extended banks of Dades river with variety of trees that embellish and decorate the oasis excluding palm trees. Palm trees are not cultivated there as the weather is quite cold especially in winter. Dades is a melting pot in which variety of high-quality touristic attractions mingled and blended together to create irresistible glamor that pulls its visitors to fell in love with the area. These touristic attractions create fairly considerable natural and cultural heritage. Accordingly, the natural environment is well diversified (gorges, high mountains, sources, etc.), whilst, the cultural heritage is well built upon significant authentic cultural legacy (kasbahs, folklore, festivals, the religious cults and buildings, handicrafts and gastronomy). Indeed, tourism is the dynamic sector in the area. Since it benefits from various assets taking in account the richness of the cultural and natural heritage of this region, including the attractiveness of the architectural heritage, the specificity of the folklore, the finesse of the gastronomy, crafts, historic sites, and the diversity of the natural landscapes. All these potentials that are, in fact, a valuable heritage, must be integrated into the development strategy of the touristic products of DadesValley to reinforce its originality and enhance its attractiveness. In short, this article is a sort of a presentation of these characteristics with much focus on the general aspect of tourism in Dades and the useful elements for the development of a touristic mountainous area.